John Wesley's means of evangelism - Gribble, James (Rhodes University, Faculty of Divinity, Department of Divinity, 1974)
This essay is an attempt to evaluate the methods of evangelism used by John Wesley during the course of his long ministry in the eighteenth century. Wesley's methods are important, since by their use he exercised a remarkable influence upon the religious and social life of eighteenth-century England. They have a continuing importance, too, for a Church that wants to carry out her Lord's "Great Commission" effectively. In the history of the Church Wesley stands in the front rank of those who have significantly carried forward the mission of the Church. Therefore we do well to pause and learn what we can from his example and experience. Intro., p. 1.
Keywords: Wesley, John, 1703-1791; Evangelistic work Methodist Church -- Doctrines